Perspectives on Health and Health Education (Panauti Journal, 2024)
This study highlights different perspectives on health education. The naturalistic/bio-medical, functionalist, post-modernist, and Marxist perspectives on health and health education were all looked at in this study. The analysis is based on both published and unpublished materials, including online sources. Desk inquiry is the method used for analyzing the literature. Based on biological function and statistical normality, the naturalistic/bio-medical perspective regards health as belonging to a medical origin. By using an organismic illustration, the functionalist perspective emphasizes protecting social equilibrium and stability in order to explain human societies and social phenomena. While pursuing health and health education, the post-modernist perspective emphasizes the multiple realities of human health and class struggle. Each perspective offers a unique lens for understanding health and health education, emphasizing the importance of considering individual and societal contexts.